Influence of magnetite on the leaching of chalcopyrite in sulfuric acid - Sha Deng; Jiaxin Yang; Yaping Wang; Tao Long; Wei Yang (Arabian Journal of Chemistry, 2023)
Magnetite is one of the common associated minerals of chalcopyrite. However, so far, no studies have elucidated the effect of magnetite on the dissolution behaviors of chalcopyrite. In this paper, the impact of magnetite on the dissolution of chalcopyrite in sulfuric acid was investigated by leaching experiments, electrochemical measurements, XRD, Raman, and FTIR techniques. Results show that the presence of magnetite significantly enhances the dissolution of chalcopyrite. Different additions of magnetite in the leaching system of chalcopyrite contribute to remarkable differences in the redox potentials. When 0.5 g of magnetite was added, the redox potential was maintained in the range of 650–700 mV (vs. SHE) where chalcopyrite was reduced to chalcocite and then oxidized to Cu2+. But for magnetite additions of 1 g and 2 g, the redox potential exceeded the appropriate range for chalcocite formation, so the dissolution of chalcopyrite was dominated by the direct oxidation by Fe3+. Electrochemical measurements verified the existence of the galvanic interaction between magnetite and chalcopyrite, but its effect is much less than that of iron ions on chalcopyrite dissolution. The study suggests that copper extraction of chalcopyrite can be improved by the addition of proper amount of magnetite.